2021
DOI: 10.1002/jsfa.11619
|View full text |Cite
|
Sign up to set email alerts
|

Growth stage and ensiling: impact on chemical composition, conservation quality and in situ ruminal degradability of whole‐crop oat

Abstract: BACKGROUND The effects of growth stage (GS) and ensiling were assessed on whole‐crop oat's (Avena sativa L. cv. Cantara) chemical composition, silage fermentation quality and in situ ruminal degradability. Oat was harvested and ensiled at six GS: boot, heading, water ripe, early milk, early dough and grain ripe (144, 151, 178, 234, 362 and 512 g kg−1 of dry matter (DM) of whole‐crop forage, respectively). RESULTS GS influenced chemical composition, silage fermentation quality and ruminal degradability of whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The growth stage had been characterized as the main factor affecting silage quality because the dry matter (DM) production, ensilability, chemical composition, and nutritive value of forage are varied along with its change ( Nazli et al, 2019 ). Early harvest crops were more suitable for ensiling because of higher water-soluble carbohydrates (WSC) ( Stirling et al, 2021 ), but they showed a lower DM yield than delayed harvest ( Xie et al, 2012 ). Besides, clostridial activity will be encouraged by the high moisture content of early harvested crops, resulting in considerable DM and energy losses ( McDonald et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…The growth stage had been characterized as the main factor affecting silage quality because the dry matter (DM) production, ensilability, chemical composition, and nutritive value of forage are varied along with its change ( Nazli et al, 2019 ). Early harvest crops were more suitable for ensiling because of higher water-soluble carbohydrates (WSC) ( Stirling et al, 2021 ), but they showed a lower DM yield than delayed harvest ( Xie et al, 2012 ). Besides, clostridial activity will be encouraged by the high moisture content of early harvested crops, resulting in considerable DM and energy losses ( McDonald et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such variations in the chemical composition of the forage might be attributed to the geographical location, plant varieties, climate, season of harvest and fertilization 22 . Similarly, Stirling et al 23 . found that the WSC contents in whole‐crop oat decreased from the heading stage (49.5 g kg −1 DM) to the water ripe stage (33.5 g kg −1 DM).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that the growth stage (or harvest time) was an important factor affecting the chemical composition of grasses ( Stirling et al., 2022 ). In the early stages of growth, the leaves have a high proportion of the whole plant in grasses.…”
Section: Discussionmentioning
confidence: 99%